Pengaruh Good Corporate Governance, Return On Equity, Kinerja Lingkungan, Dan Leverage Terhadap Corporate Social Responsibilitty - Sasanti, Elin Erlina; Animah, Animah; Nabila, D. Tialurra Della (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
This study aims to determine the effect of good corporate governance, return on equity, environmental performance, and leverage on Corporate Social Responsibility (CSR). The population in this study were mining companies listed on the Indonesia Stock Exchange in 2016-2018. The research sample was determined based on purposive sampling method. The data used are secondary data in the form of annual financial reports obtained from www.idx.co.id. Data were analyzed using descriptive statistics, classical assumptions and multiple regression analysis. The results showed that good corporate governance as proxied by the Asean Corporate Governance Score has an effect on CSR, while return on equity, environmental performance and leverage have no effect on CSR. The implication of this research is that when companies applied the ACGS index, the level of social responsibility disclosure tend to decrease. Although CSR has a voluntary nature for companies in Indonesia, nevertheless in the case of mining sector companies, they basically will have a broader disclosure since they are more related to their environment. Hence, further research is expected to make environmental performance as a moderating variable.